An Ecolinguistic Discourse Analysis of the BBC's Nature Documentary Series Planet Earth and Planet Earth II - Nikkanen, Jussi (My University, 2024)
The aim of this thesis is to study the language that is used in the narration of the BBC’s television nature documentary series Planet Earth (2006) and Planet Earth II (2016). The narration is analysed from a critical ecolinguistic point of view, and the focus is on the language elements that either implicitly or explicitly make it positive, destructive or – in the case that it entails both positive and destructive qualities – ambivalent discourse. The data of this research consists of instances that discuss human-made environmental issues or use features of language that portray different animal species and natural areas either positively or negatively and therefore might affect the ecological philosophy of the audience. Additionally, the narration of the two series is compared with each other to determine whether the more recent series includes more instances of positive discourse, as environmental issues are increasingly topical in today’s world. The results show that both series include more positive than destructive discourse. The main ways in which the narration is positive include stating that human influence on nature is detrimental, using language features that evoke a sense of solidarity, using positively connoted lexical words, referring to animals using the personal pronouns she and he, and personification of natural areas. The results also indicate that the newer series has more instances of positive discourse per episode, but it also includes more instances of ambivalent discourse; the environmental issues are discussed more extensively, yet the human part in these issues is often disregarded.
Keywords: Ecolinguistics, discourse analysis, positive discourse analysis, critical discourse studies, television documentary